Integralna korporativna varnost: Praktikum - Miha, Miha (University of Maribor Press, 2024)
Integral Corporate Security: Practicum. Security is generally one of the most important elements of humanity, so an activity called corporate security has also developed in organizations, which ensures security in various areas. Regardless of its importance, it is still not given enough attention. That is why the practicum presents different views on the concept itself, its beginnings or history and everything that actually makes up the complete process of ensuring security in organizations. Through the practicum, the reader gets acquainted with everything that is important in ensuring the safety of persons, property, infrastructure and everything else that makes up corporate security. By presenting all concepts, definitions, procedures and processes, the understanding of the basic concept becomes much easier, which helps to answer more easily the questions that are asked after each chapter. Through the questions, the reader consolidates his knowledge, and at the same time we hope that it arouses in him an even greater interest in the field of corporate security.